Strategies for Household Waste Management in Winong Village Waste Bank: Strategi Pengelolaan Sampah Rumah Tangga di Bank Sampah Winong - Phahlevy, Rifqi Ridlo; Ni’mah, Mufidatun (Indonesian Journal of Law and Economics Review, 2024)
Background: Legal frameworks are vital for guiding village autonomy and waste management practices. Specific Background: In Indonesia, laws such as Law No. 6/2014 and Law No. 18/2008 regulate these areas but face implementation challenges. Knowledge Gap: There is a lack of integration between community perspectives and local governance practices. Aims: This study analyzes the legal foundations of waste management in rural settings and assesses practical implementation through stakeholder input. Results: Using a normative legal approach alongside Focus Group Discussions with various stakeholders, the research identifies gaps in the application of waste management laws and emphasizes the need for tailored legal recommendations. Novelty: By merging legal analysis with empirical insights, the study provides a comprehensive view of waste management in rural contexts. Implications: Findings highlight the necessity for adapting legal frameworks to local systems and engaging communities, offering practical solutions for rural waste management that contribute to environmental governance. Highlights : Legal Foundations: Examines laws governing waste management and village autonomy. Stakeholder Input: Utilizes Focus Group Discussions to gather community perspectives. Contextual Adaptation: Emphasizes the need for tailored legal solutions for effective implementation. Keywords: legal frameworks, waste management, village governance, community engagement, empirical analysis